Evaluation of the Changes in the Alveolar Bone and Root Length after Maxillary Anterior Tooth Retraction and the Factors Influencing Them - S. Harinarayanan; Sanju Somaiah; B. Goutham; Sunil Muddaiah (Contemporary Clinical Dentistry)
Introduction: There is a scarcity of studies in which both alveolar bone remodeling and root resorption are simultaneously assessed and compared against possible influencing factors such as rate of retraction and change in inclination. The aim of our study was to assess the changes in the alveolar bone thickness and root length of the maxillary anterior teeth after retraction and correlate it to the potential influencing factors, namely rate of retraction and change in inclination. Subjects and Methods: Ten patients requiring upper premolar extraction as part of their treatment were included in the study. Alveolar bone and root length changes were measured using cone beam computed tomography and the rate of retraction and change in inclination were assessed using lateral cephalograms. Two readings: Preretraction and postretraction were taken. Statistical analysis was done using Paired rank t-test and Spearman’s rank correlation tests. Significance level was set at P < 0.05. Results and Conclusions: The labial alveolar bone thickness showed an increase, whereas the palatal and total alveolar bone thickness showed a decrease. Root resorption was observed in all teeth. Alveolar bone changes showed a positive correlation to the rate of retraction and a negative correlation to the change in inclination. The root length change showed a positive correlation to the change in inclination.